ACCESSIBILITY IN BASIC HEALTH UNITS: A LOOK AT THE ELDERLY PERSON (REMUNOM, 2023)
This work had the objective of identifying and analyzing how the lack of accessibilityof the Basic Health Units interferes in the care of the elderly, since, according to theBrazilian Institute of Geography and Statistics (IBGE), the population segment thatincreases the most in the population Brazilian is that of elderly people, with growthrates of more than 4% per year for the decade from 2012 to 2022, representing, inthe same period, an average increase of more than 1 million elderly people per year.Accessibility is a constant concern for the elderly, and with the increase of this publicin the country, the concern with access to health grows together, both with regard tothe infrastructure of these Units, and in relation to the humanized reception. The termaccessibility, which was discussed in this study, was related to the ease of usinghealth services, thus promoting integrality, equity, universality and socialparticipation. This study primarily consists of analyzing these difficulties, aiming at animprovement to be adopted, in which there is relevant prioritization to those whoneed shelter, especially the elderly, in order to be able to positively interfere in thehealth status of this public. For that, a qualitative methodology was used, based onstudies related to the theme. As a research technique for data collection andanalysis, a bibliographic review was used, with the intention of describing the objectof study. In the end, the importance of accessibility was considered for the quality ofcare for the elderly in the UBS, inserting it in a comprehensive and individualizedview, seeking to help them within their needs. It was evidenced how adequateassistance, trained professionals, adapted spaces bring more security and comfort inthe care of the elderly, who with this can realize their importance in society and thustake care of their health in a more humane way.